(untitled) (Biological Sciences - PJSIR, 2005)
Three different experimental methods were used to analyse iron content in groundwater samples drawn from various spots of Mirzapur, a southeastern part of Rajshahi City, Bangladesh. These included UV-visible spectrophoto- metry, atomic absorption spectrophotometry, and titrimetric methods. As many as 20 water samples were collected from randomly selected domestic water supply tubewells throughout the area. Iron content was found to range between 0.052 - 5.890 ppm, 0.060 - 6.060 ppm, and 0.139 - 5.584 ppm by the spectrophotometric, atomic absorption spectro- photometric, and titrimetric methods, respectively. The values obtained with the three different methods were, fairly comparable and lie within the fringe of experimental deviations.